Influence of psoriasis on infection risk and survival outcomes in patients with head and neck cancer: a retrospective cohort study - Lin Jian; Mu-Kuan Chen; Chew-Teng Kor; Yen-Tze Liu (BMC Cancer)
Abstract Background Psoriasis is a chronic inflammatory skin condition mediated by autoimmune processes, which may heighten the susceptibility to infections. However, its impact on infection risk and survival outcomes in patients with head and neck cancer (HNC) remains understudied. Methods We conducted a retrospective cohort study using data from a tertiary referral center in Taiwan between January 2010 and August 2021. A total of 4,476 HNC patients were identified, of whom 49 had psoriasis and 4,427 did not. After propensity score matching (PSM), 48 patients with psoriasis and 480 without psoriasis were included in the final analysis. The primary outcome was the one-year post-treatment infection rate, assessed using hazard ratios (HRs) derived from Cox proportional hazards models. Secondary outcomes included overall survival (OS) and disease-free survival (DFS). Subgroup and sensitivity analyses were performed based on psoriasis severity and systemic therapy use. Results The one-year infection rate was significantly higher in the psoriasis group compared to the non-psoriasis group (33.3% vs. 20.2%, P = 0.035), with a hazard ratio (HR) of 1.84 (95% CI: 1.09–3.11). Psoriasis patients on systemic therapy had an elevated infection risk (HR: 1.99, 95% CI: 1.12–3.53, P = 0.0189). Sensitivity analysis confirmed a consistent association between psoriasis and infection risk (HR: 2.04, 95% CI: 1.18–3.51, P = 0.0106). Psoriasis did not significantly impact survival outcomes. Conclusions Psoriasis is associated with an increased one-year infection risk following HNC treatment, particularly in patients receiving systemic therapy. This finding suggests a need for heightened infection monitoring and preventive care in HNC patients with psoriasis.